Prevalence of rheumatic heart disease among school children in Ethiopia: A multisite echocardiography-based screening. (15th October 2016) - Yadeta, Dejuma; Hailu, Abrha; Haileamlak, Abraham; Gedlu, Etsgenet; Guteta, Senbeta; Tefera, Endale; Tigabu, Zemene; Tesfaye, Hagazi; Daniel, Wandimu; Mekonnen, Desalew; Zelalem, Meseret; Tekleab, Yohannes; et al.
Abstract: Background: Auscultation-based surveys in Ethiopia conducted in the late 1990's reported a rural prevalence of 4.6/1000 and an urban prevalence of 6.4/1000 of rheumatic heart disease (RHD). With echo-based screening, we aimed to estimate the national prevalence of RHD in school children by taking school-based samples from six regions across the country using the 2012 World Heart Federation echocardiographic criteria. Patients and methods: We conducted a cross-sectional echocardiographic screening of RHD in school children aged 6–18 years from 28 randomly selected primary and secondary schools found in six different geographic regions of Ethiopia. We used the standardized WHF echocardiographic criteria. Results: A total of 3238 children (48.5% females) were screened. The mean age was 13.2 ± 3.2 years. Of these, 44 patients (1.4%) met the WHF criteria for definite RHD, while 15 (0.5%) met the criteria for borderline disease, yielding a prevalence of 19 [13.9–23.4, 95% CI] cases per 1000 school children between the ages of 6–18 years. The majority of those who tested positive were girls (26/44). The prevalence was lowest in children aged 6–9 years and otherwise uniformly distributed across ages 10–18 years. Definite RHD involved the mitral valve in 42 subjects, 39 of whom had mitral regurgitation and 3 with mitral stenosis. The aortic valve was affected in 6 children. The ratio of definite to borderline cases was 2.9. Conclusion: This study demonstrated a consistent pattern of high prevalence of asymptomatic RHD with definite disease predominating over borderline involvement across six regions of Ethiopia.